Means of Evidence in the Contested Procedure - Qerkini, Artan (European Journal of Multidisciplinary Studies, 2018)
This research paper addresses means of evidence in contested procedure, through describing and analyzing all means of evidence recognized under the Law No. 03/L-066 for the Contested Procedure in Kosovo (hereinafter LCP). This research, amongst others, provides for a comparative overview on certain important issues between LCP, the old Law on Contested Procedure in Kosovo which was in force until 2008, and the Code of Civil Procedure of Albania (hereinafter CCPr). Nonetheless, despite containing comparative elements, the research, in its entirety, aims to elaborate the means of evidence in line with LCP, while highlighting the strengths and weaknesses of relevant legal dispositions in Kosovo covering this matter. This paper will initially define means of evidence, the importance these means have on determining relevant and contentious facts between litigants, universally recognized facts as well as facts which must be necessarily determined through means of evidence. Following this, this paper will elaborate other institutes relevant for the contested procedure, as: object of evidence, obtainment and assessment of evidence, etc. This paper will initially provide a description and explanation of means of evidence foreseen under LCP of the Republic of Kosovo. Given that it is precisely the evidence administered in a contested procedure what gives direction to determining the merits of the case in a certain matter, this paper pays particular attention to evidence obtaining methods, starting from examination, evidence administration through experts, and party hearing. This research paper humbly acknowledges that it does not suggest that all elements and matters concerning means of evidence in contested procedure have been covered. Nonetheless, we are confident that it does cover the fundaments of the addressed topic.
Keywords: means of evidence, contested procedure